2015
DOI: 10.2478/raon-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Hürthle cell carcinoma soon after surgical extirpation of Hürthle cell adenoma and follicular adenoma of the thyroid gland

Abstract: BackgroundHürthle cell neoplasms could be benign (Hürthle cell adenoma) or malignant (Hürthle cell carcinoma). Hürthle cell carcinoma is a rare tumour, representing 5% of all differentiated thyroid carcinomas. The cytological evaluation of Hürthle cell neoplasms by fine needle aspiration biopsy (FNAB) is complicated because of the presence of Hürthle cells in both Hürthle cell adenoma and Hürthle cell carcinoma. Thus, the preoperative distinction between these two entities is very difficult and possible only w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Pathologists in the past were reluctant to classify HCN as benign due to the known aggressive nature of HCC [60], but subsequent studies have demonstrated that histologic criteria can reliably differentiate HCA from HCC [61]. A case of HCA with atypia and follicular adenoma recurring as HCC suggested that total thyroidectomy be performed for large HCA >1 cm with cellular atypia, or if multiple bilateral nodules are detected [62]. We agree with the approach of total thyroidectomy for those with bilateral nodules, as our patient also had bilateral nodules detected at the initial visit but underwent two separate hemithyroidectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologists in the past were reluctant to classify HCN as benign due to the known aggressive nature of HCC [60], but subsequent studies have demonstrated that histologic criteria can reliably differentiate HCA from HCC [61]. A case of HCA with atypia and follicular adenoma recurring as HCC suggested that total thyroidectomy be performed for large HCA >1 cm with cellular atypia, or if multiple bilateral nodules are detected [62]. We agree with the approach of total thyroidectomy for those with bilateral nodules, as our patient also had bilateral nodules detected at the initial visit but underwent two separate hemithyroidectomies.…”
Section: Discussionmentioning
confidence: 99%